1988
DOI: 10.1002/jmv.1890260310
|View full text |Cite
|
Sign up to set email alerts
|

Protection against acute lethal viral infections with the native steroid dehydroepiandrosterone (DHEA)

Abstract: A significant protective effect of a native adrenal steroid, dehydroepiandrosterone (DHEA), was demonstrated in studies of two lethal viral infection models in mice: systemic coxsackievirus B4 and herpes simplex type 2 encephalitis. The steroid was active either by long-term feeding or by a single subcutaneous injection. A closely related steroid, etiocholanolone, was not protective in these models. Histopathological analysis, leukocyte counts, and numbers of spleen antibody forming cells in the coxsackievirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(85 citation statements)
references
References 59 publications
2
82
0
1
Order By: Relevance
“…Exogenous administration of DHEA has been reported to decrease mortality in mice with systemic coxsackievirus B4 infection and with herpes simplex type 2 encephalitis. 15 Decreased DHEA levels have been inversely correlated with progression of disease in HIV and human Tcell lymphotropic virus type I (HTLV-1) infections. 2,3,16 Furthermore, decreased DHEA levels in the elderly have been implicated, at least in part, in age-related immunosenescence.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous administration of DHEA has been reported to decrease mortality in mice with systemic coxsackievirus B4 infection and with herpes simplex type 2 encephalitis. 15 Decreased DHEA levels have been inversely correlated with progression of disease in HIV and human Tcell lymphotropic virus type I (HTLV-1) infections. 2,3,16 Furthermore, decreased DHEA levels in the elderly have been implicated, at least in part, in age-related immunosenescence.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated in vitro and in vivo that DHEA can restore the age-related, defective TNF-␣ production in macrophages and mitogen-induced splenocyte proliferation [12]. May et al [23] demonstrated that DHEA administration reversed corticosteroid and stress-induced inhibition of immune function, Loria et al [24] showed that DHEA administration has a protective effect against systemic Coxsackie virus and Herpes simplex type 2 encephalitis, and Daynes et al [25] found that it can enhance IL-2 production by activated murine T cells. In a limited clinical trial, it has been demonstrated that orally administered DHEA (50 mg/daily) to elderly men with low-serum DHEA safely activated several immune functions within 2-20 weeks of treatment, including B and T cell mitogenic response and PHA-induced IL-2 production, suggesting potential therapeutic benefits of DHEA supplementation in immunodeficient states [26].…”
Section: Discussionmentioning
confidence: 99%
“…DHEA-S is more frequently studied in social science research because it has a longer half-life than DHEA and an absence of diurnal variation (Rosenfeld, Rosenberg, Fukushima, & Hellman, 1975). DHEA and DHEA-S appear to have protective functions against a variety of conditions, including HIV (Loria, Inge, Cook, Szakal, & Regelson, 1988), Cushing's disease (Yamaji, Ishibashi, Sekihara, Itabashi, & Yanaihara, 1984), Alzheimer's disease Affectionate Communication 8 (Näsman et al, 1995), and some forms of cancer (Gordon, Helzlsouer, & Comstock, 1991).…”
Section: Affectionate Communicationmentioning
confidence: 99%